Financial Constraints and the Use of Trade Credit: Evidence from Pakistan - M. Younis; M. J. Khan; M. Y. Khan (Финансы: теория и практика, 2024)
The purpose of this study is to identify whether financially constrained firms use trade credit (payables and receivables) as a channel to finance their operations. The previous literature mainly investigated the role of trade credit in various aspects of a firm’s performance. We argue that, since firms with limited financial capabilities usually have limited or no access to the long-term debt market, they can better be expected to rely on short-term financing, such as trade credit. We use Kaplan and Zingales index (KZ Index 1997) to measure the level of firms’ financial constraints. The fixed-effects panel regression methodology was applied to a sample of non-financial firms listed on Pakistan Stock Exchange over eleven years from 2009 to 2019. The results of this article show that financially constrained firms use trade credit as a financing channel for their operations. We further found that firms with higher profit margins use more trade credit while those that have higher assets turnover use fewer loans.